Gioia's Reply to Jones and Wicks - Gioia, Dennis A. (Academy of Management Review, 1999)
The author responds to T. M. Jones and A. C. Wicks' reactions after the initial criticism of their article “Convergent Stakeholder Theory.” The author points out three major points of disagreement with Jones and Wicks' commentary on his original piece, including their academic judgments of his real-life scenarios, their assumptions about decision making practices, and general attack against a personal experience the author had. The ultimate suggestion of this response is that the reader be given the ability to make their own decisions about the theories discussed in the readings.